Yield, cluster drop and nut traits of three Turkish hazelnut cultivars - Ü. Serdar; T. Demir (Horticultural Science, 2005)
The yield, cluster drop and nut traits of the hazelnut cultivars Tombul, Palaz and Çakildak in Turkey were examined during 2001-2002. The cluster drop ranged from 7.5 to 17.0%. The highest yield per shrub with 2,930 g in 2001 and 3,190 g in 2002 was found in cultivar Tombul. This cultivar was also better in terms of the studied fruit traits compared with the other cultivars. In this cultivar (in 2001 and 2002), nut numbers per cluster were 3.87 and 3.46, nut weights were 1.53 and 1.70 g, kernel weights 0.93 and 0.99 g, and kernel proportions were 50.9 and 53.8%.